PENGARUH SKOR PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP NILAI PERUSAHAAN: PERAN MODERASI KUALITAS AUDIT DAN INOVASI TEKNOLOGI - Lisfi Dita Anggraini; Rahmat Setiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Environmental, Social, and Governance (ESG) disclosure has become an increasingly important indicator of corporate sustainability performance. However, prior studies in Indonesia show inconsistent findings regarding the effect of ESG on firm value. This study aims to analyze the influence of ESG disclosure on firm value and examine the moderating roles of audit quality and technological innovation. The research uses secondary data from 24 public companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period, comprising 120 observations (unbalanced panel data). Firm value is measured using Tobin's Q, audit quality is proxied by a Big Four audit dummy, and technological innovation is measured using R&D intensity. Moderated regression analysis is employed with firm size and leverage as control variables. The findings show that ESG disclosure has a positive and significant effect on firm value, and this effect becomes stronger when companies are audited by Big Four auditors. However, technological innovation does not moderate this relationship. This study contributes to the ESG literature in developing countries and provides practical implications for companies in enhancing firm value through sustainability practices and high-quality audits.